Understanding Canadians’ Declining Confidence in Public Education - Guppy, Neil; Davies, Scott (Canadian Journal of Education/Revue canadienne de l'éducation, 1999)
Canadians’ confidence in public education is declining. We present new evidence, both attitudinal and behavioural, confirming this trend. More significantly, we investigate several possible explanations for the trend, including demographic as well as institutional perspectives. Our analysis finds little support for demographic shifts as an explanation, but we do find that confidence in all institutions, not just public education, is waning. We compare and contrast various interpretations of these findings, building especially on the themes of the knowledge society and the risk society. We interpret these findings as showing that Canadians see schooling as increasingly important. La confiance des canadiens dans l’enseignement public n’est plus ce qu’elle était. Les au- teurs présentent de nouvelles données sur les comportements et les attitudes qui viennent le confirmer. En outre, ils se penchent surtout sur plusieurs explications possibles de cette tendance, y compris les facteurs démographiques et institutionnels. D’après leur analyse, il n’est guère possible de retenir l’explication démographique, mais ils ont effectivement pu observer la perte de confiance dans toutes les institutions, et pas seulement dans l’enseignement public. Les auteurs comparent diverses façons d’interpréter ces constata- tions en insistant tout particulièrement sur les thèmes de la société de la connaissance et de la société du risque. D’après eux, les résultats observés démontrent que les canadiens considèrent l’éducation comme étant de plus en plus importante.